Sustainable Human Resource Practices: The Effect of Leadership, Compensation and Work Spirit on Employee Performance - Hadi Rahmanda; Yunia Wardi (Dinasti Publisher, 2025)
The goal of this study is to determine how employee performance is influenced by leadership, compensation, and work spirit in an organizational environment. The (SLR) approach, a systematic review of related material from several academic sources, was the study methodology used. This research data was obtained through online searches and journals related to job satisfaction published in the 2019-2024 period. The number of journals analyzed was 21 journals. The findings of this study indicate that elements such as incentives, balanced salaries, and strong leadership styles can increase worker productivity. These results suggest that in order to increase worker productivity and satisfaction, it is imperative for companies to focus on these factors. Therefore, it can be said that achieving peak performance in the workplace largely depends on factors such as leadership, compensation, and work spirit.